Predentin's influence on clastic cell behavior in human external cervical resorption: Evidence from a case study - Toshihiro Noma; Shohei Yoshimoto; Yasuhiko Kamura; Masaki Arioka (Elsevier, 2024)
External cervical resorption (ECR) is an aggressive disease characterized by resorption of the tooth root structure. While the pericanalar resorption-resistant sheet (PRRS) impedes ECR progression towards the pulp, the underlying mechanisms of its protective role in human teeth remain unclear. This study aimed to elucidate the pathology of ECR in a 31-year-old female patient by employing radiographic, histological, and immunohistochemical analyses of an extracted tooth. Histological examination revealed that the PRRS comprised dentin, predentin, and reparative bone-like tissue. Notably, clastic cells were observed on the surfaces of all three tissues within the same specimens. Immunohistochemical staining for cathepsin K demonstrated diminished resorptive activity of clastic cells on predentin compared to dentin and bone-like tissue. These findings suggest a potential role for predentin in attenuating clastic cell activity, potentially serving as the final barrier safeguarding the pulp tissue.